Advancements in veterinary medicine: the use of Flowgy for nasal airflow simulation and surgical predictions in big felids (a case study in lions) - Burgos, Manuel; Pérez-Ramos, Alejandro; Mulot, Baptiste; Sanz-Prieto, Daniel; Esteban, Francisco; Bastir, Markus (Frontiers in Veterinary Science, 2024)
Flowgy is a semi-automated tool designed to simulate airflow across the nasal passage and to detect airflow alterations in humans. In this study, we tested the use and accuracy of Flowgy in non-human vertebrates, using large felids as the study case. Understanding the dynamics of nasal airflow in large felids such as lions (Panthera leo) is crucial for their health and conservation. Therefore, we simulated airflow during inspiration through the nasal passage in three lions (Panthera leo), two of which were siblings (specimens ZPB_PL_002 and ZPB_PL_003), without breathing obstructions. However, one of the specimens (ZPB_PL_001) exhibited a slight obstruction in the nasal vestibule, which precluded the specimen from breathing efficiently. Computed tomography (CT) scans of each specimen were obtained to create detailed three-dimensional models of the nasal passage. These models were then imported into Flowgy to simulate the airflow dynamics. Virtual surgery was performed on ZPB_PL_001 to remove the obstruction and re-simulate the airflow. In parallel, we simulated the respiration of the two sibling specimens and performed an obstructive operation followed by an operation to remove the obstruction at the same level and under the same conditions as the original specimen (ZPB_PL_001). We obtained a pattern of precision for the operation by having two comparable replicas with the obstructed and operated specimens. The simulations revealed consistent airflow patterns in the healthy specimens, demonstrating the accuracy of Flowgy. The originally obstructed and the two artificially obstructed specimens showed a significant reduction in airflow through the right nostril, which was restored after virtual surgery. Postoperative simulation indicated an improvement of > 100% in respiratory function. The temperature and humidity profiles within the nostrils also showed marked improvements after surgery. These findings underscore the potential of Flowgy in simulating nasal airflow and predicting the outcomes of surgical interventions in large felids. This could aid in the early detection of respiratory diseases and inform clinical decision-making, contributing to improved veterinary care and conservation efforts. However, further research is needed to validate these findings in other species and explore the potential of integrating Flowgy with other diagnostic and treatment tools in veterinary medicine.